2020
DOI: 10.1007/s10811-020-02138-9
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation conditions affect the monosaccharide composition in Ulva fenestrata

Abstract: In recent years, the interest in using seaweed for the sustainable production of commodities has been increasing as seaweeds contain many potentially worthwhile compounds. Thus, the extraction and refining processes of interesting compounds from seaweeds is a hot research topic but has been found to have problems with profitability for novel applications. To increase the economic potential of refining seaweed biomass, the content of the compounds of interest should be maximized, which can potentially be achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 38 publications
1
24
3
Order By: Relevance
“…Since glucuronic acid also is the main component of the glucuronan polysaccharide in U. intestinalis, the link between ulvan and geographical location cannot be confirmed, although the numerous indications lend the argument some merit. In defined tank cultivation of Ulva fenestrata, it was found that low levels of nitrate increased the content of iduronic acid and low levels of phosphate increased rhamnose content in biomass, while increased irradiance affected both the iduronic acid and rhamnose contents (Olsson et al, 2020b). It is thus apparent that ulvan content and subsequently monosaccharide content is highly variable and allows Ulva species to acclimate to changes in variation in environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since glucuronic acid also is the main component of the glucuronan polysaccharide in U. intestinalis, the link between ulvan and geographical location cannot be confirmed, although the numerous indications lend the argument some merit. In defined tank cultivation of Ulva fenestrata, it was found that low levels of nitrate increased the content of iduronic acid and low levels of phosphate increased rhamnose content in biomass, while increased irradiance affected both the iduronic acid and rhamnose contents (Olsson et al, 2020b). It is thus apparent that ulvan content and subsequently monosaccharide content is highly variable and allows Ulva species to acclimate to changes in variation in environmental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Carbohydrate content and composition were determined after acid hydrolysis of 25 mg samples according to Bikker et al (2016) without neutralization, and subsequent analysis by high-performance anion-exchange chromatography with pulsed amperometric detection (HPAEC-PAD) (Olsson et al, 2020b). The total carbohydrate content was calculated as the sum of monosaccharides and sugar acids corrected for the addition of water during hydrolysis of polysaccharides.…”
Section: Analyses Of Biomass Componentsmentioning
confidence: 99%
“…Additionally, value-added products such as functional foods, cosmeceuticals, nutraceuticals and pharmaceuticals can be produced from their many bioactive compounds [34,35]. Ulva biomass can exhibit high total carbohydrate contents (15-65% dw) [27,36,37] and comprises the soluble sulphated polysaccharide ulvan. Ulvan can be used in water-conditioning hydrogels [11] and can be processed into heparin-like oligosaccharides as well as into rare monosaccharides, such as rhamnose and iduronic acid [10].…”
Section: Introductionmentioning
confidence: 99%
“…Ulvan can be used in water-conditioning hydrogels [11] and can be processed into heparin-like oligosaccharides as well as into rare monosaccharides, such as rhamnose and iduronic acid [10]. Recent studies have shown that environmental growth conditions have significant effects on the relative growth rate as well as on the biochemical composition of the abovenamed high-value compounds, e.g., [36][37][38][39][40] which underlines the importance of the optimization of cultivation conditions in aquaculture settings [40].…”
Section: Introductionmentioning
confidence: 99%
“…The overall aim of the present study was to investigate how changes in several cultivation conditions (irradiance, temperature, nitrate, phosphate, and pCO 2 ) affect the growth and levels of several commonly measured biochemical constituents (total fatty acid, protein, phenolics, ash, and biochar content) of Swedish U. fenestrata in the same study. Effects of environmental factors on the carbohydrate and ulvan content of U. fenestrata are presented in Olsson et al (2020). To achieve our aim, we conducted three manipulative experiments where the interactive and/or single effects of (1) irradiance and temperature, (2) nitrate and phosphate, and (3) pCO 2 at different levels were tested in indoor cultivation tanks with flow-through seawater.…”
Section: Introductionmentioning
confidence: 99%